If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10h + 1 = 25 + -2h Reorder the terms: 1 + 10h = 25 + -2h Solving 1 + 10h = 25 + -2h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '2h' to each side of the equation. 1 + 10h + 2h = 25 + -2h + 2h Combine like terms: 10h + 2h = 12h 1 + 12h = 25 + -2h + 2h Combine like terms: -2h + 2h = 0 1 + 12h = 25 + 0 1 + 12h = 25 Add '-1' to each side of the equation. 1 + -1 + 12h = 25 + -1 Combine like terms: 1 + -1 = 0 0 + 12h = 25 + -1 12h = 25 + -1 Combine like terms: 25 + -1 = 24 12h = 24 Divide each side by '12'. h = 2 Simplifying h = 2
| 2(3c-1)-1=2c+9 | | 4x+19=26+4x | | -11x^2-11x-11=0 | | 405-5t^4= | | 56-8x+4=-4x+16-7 | | 9x^4-9x^3-58x^2+4x-25=0 | | 5x-(3x+4)=17 | | 5x-1=x+23 | | 64x^3-729=0 | | 3X+2X+1+6=50-3 | | -2x-10=-16 | | 3x^2-27x+18=0 | | -2x-18=12+3x | | e^3x=.833333333333 | | 1.66(6x)= | | 1+4x=31 | | 2m^2+17m+22=0 | | 8c-7=5c+2 | | 4(x-y)+7= | | x-15=-3x+13 | | 6e^3x+4=9 | | 3G-22=-4-3g | | 16x^3-10x^2+14x= | | 4p^2-19p-5=0 | | 4(3e-2)=5(e+4) | | -4x+1=-47 | | 11t-13=3t-11 | | 3(4d-2)=5(3-d) | | 16-36-5= | | 28x^2-x-12=0 | | -22=x+-8 | | 6x+5=4-9 |